Pemodelan Kasus Tuberkulosis Berdasarkan Faktor Lingkungan Menggunakan Metode Geographically and Temporally Weighted Regression - Trezenki, Randa; Novia, Novia; Supangadi, Egita Riyanti; Raihan, Abiyandra Radika; Amelia, Ririn (Universitas Negeri Gorontalo, 2025)
Tuberculosis (TB) is currently a global health problem with a high number of cases and deaths, including in Indonesia, which ranks third in the world after India and China. TB cases in the Bangka Belitung Islands Province showed significant fluctuations from 2020 to 2024, indicating the influence of environmental factors on the spread of this disease. This study aims to model the influence of environmental factors, including population density, proper sanitation, and air quality, on the spread of tuberculosis in the Bangka Belitung Islands Province using the Geographically and Temporally Weighted Regression (GTWR) method. The data used in this study are secondary data from seven districts/cities with a total of 35 spatial-temporal observations. The results of the study indicate significant spatial-temporal heterogeneity in the distribution of TB cases. The GTWR model proved to be better than multiple linear regression with an Adjusted R2 value of 0.9733, a lower Akaike Information Criterion (AIC) of 447.23, and a smaller Root Mean Square Error (RMSE) of only 102.66. This study shows that population density and proper sanitation play an important role in increasing or decreasing TB cases, while air quality has a relatively stable effect. The GTWR approach is able to provide a more accurate picture of the pattern of TB spread and serves as a basis for formulating more targeted health interventions in the island region of the Bangka Belitung Islands Province.